FAKTOR PENGHAMBAT DAN PENDORONG PENERAPAN GENDER RESPONSIVESNESS DALAM PENYUSUNAN PROGRAM / PROYEK/KEGIATAN PROGRAM KEMISKINAN (STUDI PROGRAM PENGENTASAN KEMISKINAN DI KABUPATEN OGAN ILIR SUMATERA SELATAN) - Nengyanti Nengyanti; Delfiazi Puji Lestari; Isabella Isabella (Jurnal Pemerintahan dan Politik, 2019)
The long road to achieve women's empowerment and gender equality in the development of Indonesian women have traversed. Various policies and regulations have been made, two of them, a policy that requires the formulation of planning policies and development programs should be gender perspective contained in the regulation of the Ministry of Home Affairs Number 15 in 2008, about Guidelines of the implementation of Gender Mainstreaming in the Region, and Government Regulation Number 8 of 2008 about Stages, the Procedures of the Formulation, Control and Evaluation of the Implementation of the Regional Development Plan. In practice, women's empowerment still have stereotype and gender bias constraints from bureaucrats that the majority of men. Although the bureaucrats already have knowledge and even had received training on the gender perspective in development program, but in fact, they can not able to bring the gender perspective to be program in their unit as the local government working unit (SKPD). It is caused their inability to pull political interest are even more attractive for policy takers at every level of the process of formulation of development programs, so that the issues of gender inequality in development always get the weakening even exclusion so that the problem is not on the agenda at all. The process of formulation of policy issues that have a condition like this, in terms of policy referred nondecision policy formulation process. Policy makers at the top level of each unit of work even at the top levels of district government does not yet have the knowledge and concern for gender mainstreaming. Keywords: Gender, Development of gender-responsive, Public policy formulation, Nondecision.